1967
DOI: 10.1111/j.1600-0765.1967.tb01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Some histological and histochemical observations on the connective tissue of chronically inflamed human gingiva

Abstract: This investigation was undertaken during the tenure of a Research Fellowship in the Institute of Dental Surgery, University of London, and a Leverhulme Research Fellowship in the Department of Dental Science, Royal College of Surgeons of England. Some of the findings were included in a Thesis submitted to the University of London for the Degree of Doctor of Philosophy. One hundred and fifty biopsies of human gingiva, removed randomly from patients undergoing gingivectomy, were examined in the light microscope.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…Although collagen solubility (ratio; soluble/total collagen) was not altered in the AgAh induced gingival lesion, it did contain iess collagen , primarily less insoluble collagen, relative to tissue weight (expressed on a wet weight or dry weight basis). This is consistent with earlier studies demonstrating (1) a reduced hydroxyproline content of inflamed gingiva (Shultz-Haudt & Aas 1960, Flieder, Sun & Schneider 1966, Page 1972, and (11) the disorganization and disintegration of collagen bundles in the area of the inflammatory cell infiltrate, based on histologic observation (Melcher 1967, Sehroeder 1968, Valdrighi 1974. The most iikeiy mechanisms responsible for collagen loss during gingivai inflammation, as reviewed by Page & Schroeder (1973) are: (1) An increased release of specific coliagenases by various cell types in Ihe gingiva known to produce this enzyme, including epithelial cells, fibroblasts, macrophages and neutrophils , Werb & Burliegh 1974, Lazarus et al 1968, Wahl et al 1975, Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Although collagen solubility (ratio; soluble/total collagen) was not altered in the AgAh induced gingival lesion, it did contain iess collagen , primarily less insoluble collagen, relative to tissue weight (expressed on a wet weight or dry weight basis). This is consistent with earlier studies demonstrating (1) a reduced hydroxyproline content of inflamed gingiva (Shultz-Haudt & Aas 1960, Flieder, Sun & Schneider 1966, Page 1972, and (11) the disorganization and disintegration of collagen bundles in the area of the inflammatory cell infiltrate, based on histologic observation (Melcher 1967, Sehroeder 1968, Valdrighi 1974. The most iikeiy mechanisms responsible for collagen loss during gingivai inflammation, as reviewed by Page & Schroeder (1973) are: (1) An increased release of specific coliagenases by various cell types in Ihe gingiva known to produce this enzyme, including epithelial cells, fibroblasts, macrophages and neutrophils , Werb & Burliegh 1974, Lazarus et al 1968, Wahl et al 1975, Fig.…”
Section: Discussionsupporting
confidence: 91%
“…36 The neutrophil rich, necrotic, and spirochetal infiltration zones are unique to NUG. The histologic appearance of NUG is different from other gingival and periodontal diseases, [37][38][39] but it is complex and may be misleading, as cells associated with chronic lesions such as lymphocytes may be present also. These are probably due in part to a preexisting established gingivitis.…”
Section: Etiologymentioning
confidence: 95%
“…Early histochemical studies demonstrated that proteoglycans appeared to be lost from the center of inflammatory foci but were present in higher concentrations around the periphery (126). These early studies implied that, not only did the fibroblasts at the periphery of the inflammatory lesion show an increased capacity to synthesize proteoglycans, but the cells of the inflammatory infiltrate also stained strongly for the histochemical dyes used to locate the proteoglycans (126). Subsequent biochemical analyses of homogenates of inflamed human gingivae demonstrated that the amount of dermatan sulfate decreases while the content of chondroitin sulfate increases.…”
Section: Connective Tissue Matrix Changesmentioning
confidence: 99%